Development and characterization of a CRISPR/Cas9-mediated RAG1 knockout chicken model lacking mature B and T cells - Lee, Kyung Youn; Choi, Hyeon Jeong; Park, Kyung Je; Woo, Seung Je; Kim, Young Min; Han, Jae Yong (Frontiers in Immunology, 2022)
Although birds have been used historically as a model animal for immunological research, resulting in remarkable achievements, immune cell development in birds themselves has yet to be fully elucidated. In this study, we firstly generated an immunodeficient chicken model using a CRISPR/Cas9-mediated recombination activating gene 1 (RAG1) knockout, to investigate avian-specific immune cell development. Unlike previously reported immunoglobulin (Ig) heavy chain knockout chickens, the proportion and development of B cells in both RAG1+/- and RAG1-/- embryos were significantly impaired during B cell proliferation (embryonic day 16 to 18). Our findings indicate that, this is likely due to disordered B cell receptor (BCR)-mediated signaling and interaction of CXC motif chemokine receptor (CXCR4) with CXCL12, resulting from disrupted Ig V(D)J recombination at the embryonic stage. Histological analysis after hatching showed that, unlike wild-type (WT) and RAG1+/- chickens, lymphatic organs in 3-week old RAG1-/- chickens were severely damaged. Furthermore, relative to WT chickens, RAG1+/- and RAG1-/- birds had reduced serum Igs, fewer mature CD4+ and CD8+ T lymphocytes. Furthermore, BCR-mediated B cell activation in RAG1+/- chickens was insufficient, leading to decreased expression of the activation-induced deaminase (AID) gene, which is important for Ig gene conversion. Overall, this immunodeficient chicken model underlines the pivotal role of RAG1 in immature B cell development, Ig gene conversion during embryonic stages, and demonstrates the dose-dependent regulatory role of RAG1 during immune cell development. This model will provide ongoing insights for understanding chicken immune system development and applied in the fields of immunology and biomedical science.